Characteristics of Chemotherapy Side Effects in Patients with Nasopharyngeal Cancer - Fera Dilla Putri Deli; Reeny Purnamasari Juhamran; Sri Irmandha Kusumawardhani; Andi Tenri Sanna; Ahmad Ardhani Pratama; Poentoro Poentoro (CV. Inara, 2025)
This study investigates the characteristics of post-chemotherapy side effects in patients with nasopharyngeal cancer at Dr. Wahidin Sudirohusodo Hospital in Makassar during 2023. Utilizing secondary data, the research analyzes the prevalence of side effects based on gender and age. The findings reveal that male patients predominantly experience gastrointestinal (11.6%) and respiratory (16.8%) side effects, while female patients report higher rates of neuropathy (22.2%). In terms of age, adults exhibit the highest prevalence of gastrointestinal effects (12.1%) and combined effects (5.3%), whereas adolescents show significant rates of neuropathy (40.0%) and respiratory complications (60.0%). Elderly patients experience similar gastrointestinal and neuropathic toxicities (17.3% each), but at lower frequencies. Notably, no cases of nasopharyngeal cancer were reported in toddlers and children, indicating that this malignancy primarily affects older age groups. The study underscores the need for increased public awareness regarding nasopharyngeal cancer, particularly among vulnerable demographics, to promote early detection and prevention. Additionally, enhancing public knowledge about nasopharyngeal cancer and its risk factors is crucial for better understanding and management of the disease. Future research should focus on elaborating the specific side effects associated with each affected system to provide comprehensive insights into the impact of chemotherapy on nasopharyngeal cancer patients. Overall, this study contributes valuable information to the understanding of chemotherapy-related side effects in nasopharyngeal cancer, emphasizing the importance of tailored management strategies to improve patient outcomes and quality of life.